Coping with Death and Grief Through Technology - Klang, Mathias; Hård af Segerstad, Ylva; Jones, Steve; Farkas, Ashley; Lange, Patricia; Micalizzi, Alessandra; Leaver, Tama; Ess, Charles (AoIR Selected Papers of Internet Research, 2013)
Grieving is a complex, and often private, process in many social settings it is associated with a great deal of depth, seriousness and somberness. Conversely our present-day mobile, digital communication technologies and platforms are most commonly seen as playful, creative and rather shallow. However, the pervasiveness of these technologies in everyday life and communication makes them useful tools in coping with grief. The goal of the papers in this panel is to explore the ways in which technologies are used to cope with death and to explore the ways in which using technologies in this way affects the process of grief.